2016
DOI: 10.1186/s12872-016-0247-x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral artery disease and exertional leg symptoms in diabetes patients in Ghana

Abstract: BackgroundPeripheral arterial disease (PAD) is a major health problem in diabetes patients in high-income countries, but the PAD burden in sub-Saharan Africa is largely undetermined. We studied the prevalence of PAD and exertional leg symptoms in diabetes (DM) patients in a tertiary hospital in Ghana.MethodsIn a case control study design, 485 DM and 330 non-diabetes participants were recruited. PAD was diagnosed as Ankle Brachial Index (ABI) < 0.9. Edinburgh Claudication Questionnaire (ECQ) was used to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Peripheral arterial disease is a major health care problem in diabetes patients in Ghana. We reported previously that the prevalence of PAD in diabetes patients in Ghana was 26.7%, using Doppler measured ABI [ 14 ]. In sub-Saharan Africa, ABI is not routinely performed to diagnose PAD, even in high-risk diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral arterial disease is a major health care problem in diabetes patients in Ghana. We reported previously that the prevalence of PAD in diabetes patients in Ghana was 26.7%, using Doppler measured ABI [ 14 ]. In sub-Saharan Africa, ABI is not routinely performed to diagnose PAD, even in high-risk diabetes patients.…”
Section: Discussionmentioning
confidence: 99%
“…PAD, therefore, is clinically underrecognized, and management is initiated when associated with symptomatic exertional leg pain. However, most patients with PAD are asymptomatic, and, hence, relying on symptoms before initiating treatment may be less advantageous [ 2 , 14 ]. Moreover, the presence of PAD indicates generalised atherosclerosis in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, noncommunicable diseases (NCDs) like metabolic syndrome (MetS) are said to be rising alarmingly in the Ghanaian population particularly among females [1,2] and there are fears that this could worsen in the not-too-distant future because current data is suggestive that young adults with parental history of hypertension have increased risk for MetS [2]. Nurses are influential members of the healthcare team and could play a critical role reversing this rising burden of NCDs [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is now classified as a public health emergency in Sub-Saharan Africa (SSA) [2,5] and it is the leading risk factor for cardiovascular morbidity and mortality [1,2]. In Ghana, hypertension accounts for 4% of all Out-Patient Department (OPD) attendance and 4.6% of all deaths [12].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is now common in sub-Saharan African population and associated with macrovascular and microvascular complications [ 1 , 2 ]. Cardiovascular diseases are among the major causes of death in diabetes patients; however, studies have shown that microvascular disease is also associated with excess mortality [ 3 ].…”
Section: Introductionmentioning
confidence: 99%